Implementation of Aseptic Dispensing for Non-Cytostatic Injectable Drugs in the Internal Medicine Inpatient Ward of 'X' Hospital, West Java - Novita Sari; Ros Sumarny; Dian R. Laksmitawati; Waras Nurcholis (Poltekkes Kemenkes Palu, 2023)
Aseptic Dispensing activity is a procedure to minimize pharmaceutical preparations from the threats of pyrogens and contaminants. This study aims to determine the implementation of aseptic dispensing for non-cytostatic injectable drugs and the sterility of intravenous mixed preparations in the Internal Medicine Inpatient Ward of 'X' hospital, West Java for the period January - February 2022. This was a descriptive observational prospective study with a cross sectional approach. Researchers made direct observations of dispensing personnel, room and equipment as well as the process of aseptic dispensing activities including the stages of preparation, mixing, storage and disposal as well as sterility test of aseptic dispensing products. Based on the study results, it was obtained that of the 150 intravenous mixed preparations collected, there were 40 activities of diluting intravenous preparations, 100 activities of packaging into ready-to-use preparations and 10 activities of mixing intravenous preparations into infusion fluids, room suitability by 74%, preparations arrangement procedure by 68%, mixing procedure by 44%, storage procedure by 100% and disposal procedure by 63%. It can be concluded that the aseptic dispensing of non-cytostatic injection drugs in the internal medicine inpatient ward of 'X' hospital, West Java was not in accordance with the guidelines, especially at the mixing procedure stage (≤50). Compliance of dispensing personnel and room cleanliness during the process of mixing intravenous preparations need to be considered. The result of the identification of contamination during the aseptic dispensing activity of non-cytostatic injectable drugs showed that 1 in 150 samples (0.66%) was contaminated.